Impacts of organic materials amendment on the soil antibiotic resistome in subtropical paddy fields - Li, Zongming; Shen, Jupei; Wang, Fangfang; Wang, Meihui; Shen, Jianlin; Li, Yong; Zhu, Qihong; Wu, Jinshui (Frontiers in Microbiology, 2023)
The organic material amendment has been proven to change the soil antibiotic resistance genes (ARGs) profile, which may threaten human health through the food chain, but the effects and mechanisms of different organic materials on ARGs in paddy soils are less explored. In this study, a field experiment was set up with the treatments of conventional chemical fertilization (NPK) and common organic material amendment ((rice straw (RS), swine manure (SM) and biochar (BC)) to explore the effects and mechanisms. In total, 84 unique ARGs were found across the soil samples with different organic material amendment, and they conferred resistance to the major antibiotic classes. Compared with NPK, SM significantly increased the ARGs detected number and relative abundance. Higher detected number of ARGs than NPK were observed in BC, whilst BC had a lower relative abundance of ARGs than NPK. Compared with NPK, detected number decrease was observed in RS, although abundance showed no significant differences. Compared with other treatments, higher detected number and relative abundance of mobile genetic elements (MGEs) was observed in BC, indicating higher potential of horizontal gene transfer. There were significantly positive relationships between the relative abundances of total ARGs and MGEs and the bacterial abundance. And the network analysis suggested the important role of MGEs and bacterial communities on shaping the ARGs profile. Mantel test and redundancy analysis suggested that soil carbon, nitrogen and C/N were the major chemical driver of ARGs profile. The risk of ARGs spreading to the food chain should be considered when applying swine manure and biochar, which shifted the ARGs and MGEs profiles, respectively. Pre-treatment measures need to be studied to reduce the dissemination of ARGs when organic materials are applied in paddy fields.